The Impact Of The New Information Content Of The Auditor's Report On The Stock Prices Of Companies Listed On The Damascus Securities Exchange "An Analytical Study" - أبو رشيد, هائل (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to know the impact of the new information content of the independent external auditor's report on the stock prices of companies listed on the Damascus Securities Exchange, with the information it contains, which was prepared in accordance with the new and revised international auditing standards issued in 2015. this study included studying the content of the auditing reports published for a sample of joint stock companies listed on the Damascus securities Exchange in order to certify the results of their business for the years 2016, 2017 and 2018, and on the basis of which the companies were classified according to the content of the audit reports into three groups (companies that received reports Clean audit - companies got clean audit reports with Emphasis paragraphs - companies got conservative audit reports). then the study relied on studying the average share prices before and after the issuance of the new audit report in order to find out the investors ’reaction to the information published in the audit report, and the study concluded that there is an impact of the new informational content of the report on auditing the stock prices of companies listed on the Damascus Securities Exchange. The companies obtaining a clean audit report that affects the stock prices positively. As for the companies obtaining a conservative audit report, they affect the stock prices negatively. As for the Emphasis paragraphs, they do not affect the stock prices due to the method of reporting these paragraphs.